1984
DOI: 10.1002/1097-0142(19840101)53:1<86::aid-cncr2820530116>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin's lymphoma of the tonsil .A clinicopathologic study of 65 cases

Abstract: Sixty‐five patients presenting to M. D. Anderson Hospital and Tumor Institute with Stages IE and IIE primary tonsillar lymphoma between 1954 and 1981 were reviewed. All cases were non‐Hodgkin's lymphomas, with the majority being diffuse large cell lymphoma (85%). Initial therapy was radiotherapy alone in 54 patients, radiotherapy combined with chemotherapy in 8 patients, and chemotherapy alone in 3 patients. Stage was the most important prognostic factor, with 86% and 41% 5‐year survivals for Stages IE and IIE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
19
3
4

Year Published

1985
1985
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 35 publications
(2 reference statements)
7
19
3
4
Order By: Relevance
“…In our study, Waldeyer's ring N H L had a somewhat higher survival than extranodal and nodal NHL, but the difference was not statistically significant. Some authors have found a better prognosis in stage I than in stage I1 (3)(4)(5)(6)(8)(9)(10) head and neck NHL but this could not be verified in the present study. One reason may be that our patients were distributed over a long time period which might have influenced the staging.…”
Section: Discussioncontrasting
confidence: 95%
“…In our study, Waldeyer's ring N H L had a somewhat higher survival than extranodal and nodal NHL, but the difference was not statistically significant. Some authors have found a better prognosis in stage I than in stage I1 (3)(4)(5)(6)(8)(9)(10) head and neck NHL but this could not be verified in the present study. One reason may be that our patients were distributed over a long time period which might have influenced the staging.…”
Section: Discussioncontrasting
confidence: 95%
“…Due to frequent relapses, both in nodal and extranodal sites, and usually distant from the primary site, only half of WR NHL patients remain disease free, and 0s of W R NHL patients at 10 years is poor. The observed DFS of our patients corresponds well with results from other series on WR NHL patients mainly treated with radiotherapy(24), as does the observation that 50% of patients who are locally treated relapse. (3;…”
mentioning
confidence: 99%
“…Tonsil tutulumu gösteren non-Hodgkin lenfomalarda ortalama hasta yaşı 59 olarak bildirilmiştir [4]. Lenfoma tutulumu gösteren vakalarımızda, literatürle uyumlu olacak şekilde ortalama hasta yaşı 55.52 ± 20.66 olarak saptanmıştır.…”
Section: Bulgularunclassified